SIMULTANEOUS DETERMINATION OF KETOPROFEN AND ACETAMINOPHEN IN FIXED-DOSE COMBINATION FORMULATIONS BY FIRST-ORDER DERIVATIVE SPECTROSCOPY: APPLICATION TO DISSOLUTION STUDIES - MEDINA, JOSE RAUL; GARCIA, CLAUDIA ALEJANDRA; Hurtado, Marcela; DOMINGUEZ-RAMIREZ, ADRIANA MIRIAM (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: To develop and validate a new and easy zero-crossing derivative method for the simultaneous determination of ketoprofen and acetaminophen in fixed-dose combination formulations and to demonstrate its application in dissolution studies. Methods: Measurement was achieved using the first derivative signals at 243.2 nm for ketoprofen and at 260.5 nm for acetaminophen. The method was validated according to ICH guidelines. The proposed method was applied for the simultaneous quantification of both drugs in samples taken during the study of dissolution profiles (USP Apparatus 2, 75 rpm and 900 ml of 0.1 M phosphate buffer pH 7.4) of BifebralÂ® reference product (100/300 mg ketoprofen and acetaminophen, respectively). Samples were also analyzed by a previously validated HPLC-PDA method. Dissolution profiles were compared by similarity factor f2. Additionally values of: t50%, t85%, dissolution efficiency and mean dissolution time, obtained for ketoprofen and acetaminophen using UV and HPLC-PDA methods, were compared by Student's t-test. Results: The first derivative spectrophotometric method was linear in the range of 25â€“200 Âµg/ml for ketoprofen and 25â€“150 Âµg/ml for acetaminophen (R2>0.99, *P<0.05). The within-day and between-day precision and accuracy were within the acceptable criteria (RSD<3.4% and 100Â±3%). Similarity factor f2 was 85.85 and 88.49 for ketoprofen and acetaminophen, respectively. No significant differences between data obtained with UV and HPLC-PDA methods were found (*P>0.05). Conclusion: The proposed method can be used for the simultaneous determination of ketoprofen and acetaminophen, from fixed-dose combination formulations, in dissolution studies. The method is rapid, simple, accurate, and precise without the need of high-cost investment. Keywords: Ketoprofen, Acetaminophen, Derivative spectroscopy, Zero-crossing method, Dissolution studies. Â